FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKTIVITAS BONGKAR MUAT BATUBARA PADA PELABUHAN TANJUNG INTAN CILACAP - Frilia Esti Anggraeni; Indriyani (Saintara: Jurnal Ilmiah Ilmu-Ilmu Maritim, 2017)
The purpose and the hypothesis of this research is aim to analyze the effect of variable the readiness of infrastructure (X1), availability of coal (X2), and performance of employees (X3), to the variable stevedoring productivity (Y). This object of this research is taken by crew of coal’s ship, stevedoring worker, and employees of the PT. Pelabuhan Indonesia III (Persero) Branch ofTanjung Intan Cilacap with total 76 respondents. The data analysis is using Regression model tools SPSS Version 22,0. The result from this analysis is the readiness of infrastructure, availability of coal, and performance of employees, have positive and significant impact to the variable stevedoring productivity. The output from variable the readiness of infrastructure, availability of coal, and performance of employees, have impact on the variable stevedoring productivity with amount 69,4%, while the rest 30,6% influenced other variables outside the study.